2007
DOI: 10.1371/journal.pone.0000148
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor mRNA Expression in the Regenerating Antler Tip of Red Deer (Cervus elaphus)

Abstract: Deer antlers are the only mammalian organs that can fully regenerate each year. During their growth phase, antlers of red deer extend at a rate of approximately 10 mm/day, a growth rate matched by the antler nerves. It was demonstrated in a previous study that extracts from deer velvet antler can promote neurite outgrowth from neural explants, suggesting a possible role for Nerve Growth Factor (NGF) in antler innervation. Here we showed using the techniques of Northern blot analysis, denervation, immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 34 publications
4
27
2
Order By: Relevance
“…In contrast to the large body of literature on the role of peripheral nerves in the development of other tissues (Kumar and Brockes, 2012; Li et al, 2007), relatively few studies have investigated the function of peripheral nerves in the developing skeleton. Primary afferent sensory and sympathetic axons are known to cover the entire periosteal bone surface, are present in mineralized bone at the regions of highest metabolic activity, and reach deep into the marrow space (Bjurholm et al, 1988; Hill and Elde, 1991; Hukkanen et al, 1992; Mach et al, 2002; Wojtys et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the large body of literature on the role of peripheral nerves in the development of other tissues (Kumar and Brockes, 2012; Li et al, 2007), relatively few studies have investigated the function of peripheral nerves in the developing skeleton. Primary afferent sensory and sympathetic axons are known to cover the entire periosteal bone surface, are present in mineralized bone at the regions of highest metabolic activity, and reach deep into the marrow space (Bjurholm et al, 1988; Hill and Elde, 1991; Hukkanen et al, 1992; Mach et al, 2002; Wojtys et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the cascade of events leading to rapid growth and osteogenic activity, current research has focused on identifying and characterizing trophic factors present in the regeneration phase of this organ. Besides, the effects of hormones, growth factors such as insulin-like growth factor, epidermal growth factor, vascular endothelial growth factor, nerve growth factor, as well as bone morphogenetic proteins, have been shown to play important roles in regeneration processes of deer antler [1,4,10,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic supply of the pedicle is derived from the second cervical nerve, while the antler normally lacks a sympathetic innervation, except for (long-lived) antlers of castrates (114). There is evidence that nerve growth factor (NGF) promotes the outgrowth of the nerve fibers of the regenerating antler (115,116) and it has been suggested that NGF produced by smooth muscles of arteries and arterioles provides a guidance cue defining the track followed by the outgrowing nerve fibers (115). However, also other as yet unidentified molecules appear to be involved in promoting nerve fiber growth (116).…”
Section: The Role Of Nerves In Regenerationmentioning
confidence: 99%